The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/jcop.20363
|View full text |Cite
|
Sign up to set email alerts
|

Self‐stigma and coming out about one's mental illness

Abstract: Self-stigma can undermine self-esteem and self-efficacy of people with serious mental illness. Coming out may be one way of handling self-stigma and it was expected that coming out would mediate the effects of self-stigma on quality of life. This study compares coming out to other approaches of controlling self-stigma. Eighty-five people with serious mental illness completed measures of coming out (called the Coming Out with Mental Illness Scale, COMIS), self-stigma, quality of life, and strategies for managin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
135
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(150 citation statements)
references
References 50 publications
3
135
0
8
Order By: Relevance
“…These contexts include physical (Fife and Wright, 2000) and mental illness (Kroska and Harkness 2006;Markowitz 1998), sexual orientation (Hereck et al, 2009), and criminality (Rasmusen1996; Schnittker and John 2007). Corrigan et al (2010) identified two types of stigma: social and self-stigma. Social stigma involved discrimination at the hand of others due to illness and was a means of endorsing specific stereotypes within society.…”
Section: Background Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…These contexts include physical (Fife and Wright, 2000) and mental illness (Kroska and Harkness 2006;Markowitz 1998), sexual orientation (Hereck et al, 2009), and criminality (Rasmusen1996; Schnittker and John 2007). Corrigan et al (2010) identified two types of stigma: social and self-stigma. Social stigma involved discrimination at the hand of others due to illness and was a means of endorsing specific stereotypes within society.…”
Section: Background Literaturementioning
confidence: 99%
“…Social stigma involved discrimination at the hand of others due to illness and was a means of endorsing specific stereotypes within society. Self-stigma entailed a person discrediting him or herself, thereby endorsing the negative beliefs held by society (Corrigan et al 2010). Similarly, other scholars described self-stigmatization as the negative reaction of a person to him/herself in the light of personal experience (Knight et al, 2003).…”
Section: Background Literaturementioning
confidence: 99%
“…Programs focusing on contact with individuals with mental illness such as In Our Own Voice (IOOV)-which is a 30 -to 90-minute anti-stigma program that comprises a set of face-to-face challenges mimicking those individuals with mental illness face-has been effective in changing individuals' attitudes toward mental illness (Corrigan et al, 2010). Education programs for changing societal attitudes about mental illness have been mixed.…”
Section: Efforts To Change Attitudes Towards Mental Illnessmentioning
confidence: 99%
“…A internalização do estigma ocorre à medida que o indivíduo se torna consciente dos estereótipos negativos que as outras pessoas endossam (consciência dos estereótipos), concorda pessoalmente com esses estereótipos (concordância com estereótipos) e, aplica esses estereótipos a si mesmo. A consciência do estigma é um componente necessário, mas não suficiente para sua internalização, a qual só ocorre mediante a concordância e aplicação dos estereótipos pelos indivíduos portadores da condição estigmatizada a si próprios 19 . Nessa perspectiva, os participantes do estudo demonstraram forte o autoestigma.…”
Section: Vivendo O Autoestigma Do Alcoolismounclassified